2017
DOI: 10.4038/cbj.v8i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Is SAFTA Desirable? Evidence from Static Theory

Abstract: South Asian Free Trade Area (SAFTA) depicts a huge potentiality in expanding intra-regional trade leading to a net trade creation for the region. Yet, prevailing inter-state political disputes and inner-state conflicts within the region tend to hinder intra-regional trade. Lack of prior studies that concentrate on these political factors when assessing the desirability of South Asian trade agreements motivates the present study. Thus, this study investigates the trade creation and trade diversion effects of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Their results indicated that all the standard gravity variables are significant and confirmed the existence of trade creation effects following SAFTA. Peiris et al (2017) investigated the trade creation and trade diversion effects of SAFTA, especially after controlling the political factors. The results of the study confirmed significant intra-bloc and extra-bloc trade expansions following the agreement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Their results indicated that all the standard gravity variables are significant and confirmed the existence of trade creation effects following SAFTA. Peiris et al (2017) investigated the trade creation and trade diversion effects of SAFTA, especially after controlling the political factors. The results of the study confirmed significant intra-bloc and extra-bloc trade expansions following the agreement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in order to estimate trade creation and trade diversion effects, two dummy variables are introduced accordingly. Following Peiris et al (2017), Magee (2008), Martinez-Zarsozo et al (2009), and Moinuddin (2013), several other commonly used sets of dyad variables are introduced to the standard gravity model. Country pair per capita GDP values are used to represent the income levels of respective countries.…”
Section: Augmenting the Standard Gravity Modelmentioning
confidence: 99%
See 3 more Smart Citations